Influence of the physical structure of an invasive barnacle in structuring macroinvertebrate assemblages - Mendez, María Martha (2017)
Many invertebrate species use the microhabitats generated by barnacles to settle and to avoid predation and desiccation. In Argentina, the acorn barnacle Balanus glandula not only colonizes rocky shores but has also successfully invaded soft bottom salt marshes, where it form large three-dimensional structures that facilitate the presence of other invertebrates, thus affecting the whole species assemblage. Artificial barnacles were deployed on a Patagonian salt marsh to reproduce the physical structure of natural aggregates. The experiment included natural and material controls and two levels of structural complexity that represent the variety of aggregates found in nature: (i) aggregates with internal empty spaces and galleries among barnacles and (ii) aggregates without spaces and galleries. After nine months, the macroinvertebrate assemblages were compared between treatments. The results showed that the composition of the assemblage differed significantly between artificial treatments and control plots. However, there was no effect of the mimic barnacles on macroinvertebrate richness and diversity. In this way, our results suggest that the physical structure of B. glandula could modify the composition of macroinvertebrate assemblages. Besides, B. glandula recruits were registered on the mimics highlighting the importance that the physical structure supplied by this species could have on its own persistence within invaded soft bottom salt marshes.